Comparative study of the composition of cultivated, naturally grown Cordyceps sinensis, and stiff worms across different sampling years - Zhou, Yujue; Wang, Min; Zhang, Hui; Huang, Zhuo; Ma, Jun (PLOS ONE, 2019)
Natural Cordyceps sinensis, which is a valuable anti-tumor, immunomodulatory, and antiviral agent in Asia, has been overexploited in recent years. Therefore, it is important for cultivated C. sinensis to be recognized in the market. In this research, the main components of entirely cultivated, naturally grown C. sinensis, and stiff worms across different sampling years were detected and compared by HPLC-MS and UV spectrometry. The results indicated that the mean levels of adenosine and cordycepin were significantly higher, whereas the mean levels of mannitol and polysaccharides were remarkably lower in the cultivated type than in the natural type. No distinct difference in the average soluble protein content was observed. The composition of the stiff worms was similar to that of the natural herb, except that the total soluble protein content was higher, and that of mannitol was lower. In addition, the ultraviolet absorption spectroscopy of the three types showed high similarity at 260 nm. This research indicates that the main nutritional composition of cultivated and natural C. sinensis is identical and that cultivated type can be used as an effective substitute.